Development of strongly absorbing S, N-heterohexacene-based donor materials for efficient vacuum-processed organic solar cells. Issue 17 (11th January 2016) - Wetzel, Christoph; Mishra, Amaresh; Mena-Osteritz, Elena; Walzer, Karsten; Pfeiffer, Martin; Bäuerle, Peter
Abstract : A new class of A–D–A molecular donor materials based on planar S, N -heterohexacenes is developed for vacuum-processed planar and bulk-heterojunction solar cells providing promising power conversion efficiencies up to 7.1%. Abstract : A series of terminal dicyanovinylene (DCV)-substituted S, N -heterohexacenes with variable lengths of alkyl chains were synthesized and characterized for application in vacuum-processed planar-heterojunction and bulk-heterojunction organic solar cells. X-ray single crystal analysis of hexyl-substituted derivative4 revealed that the molecules are ordered in columns via π–π-stacking. While the influence of the alkyl chain length is negligible on the optoelectronic properties, an odd–even effect was observed with respect to the photovoltaic performance. Vacuum-processed planar-heterojunction organic solar cells prepared using DCV-substituted S, N -heterohexacenes as electron donors and C60 as the acceptor showed extraordinary high efficiencies of up to 5.0%. Bulk-heterojunction solar cells incorporating pentyl derivative3 and C60 led to excellent power conversion efficiencies of up to 7.1% exceeding those of previously reported S, N -heteropentacenes.